Online English speaking instruction in junior high schools: Readiness and obstacles - Syafryadin, Syafryadin; Santiana, Santiana (Universitas Islam Negeri Banda Aceh, 2023)
In the midst of a pandemic, teaching speaking online becomes one of the challenges. This study investigates whether or not English teachers were prepared to teach speaking virtually. Consequently, the purpose of this study was to determine the English teachers' readiness and obstacles to teaching speaking online during the pandemic Covid-19. The researcher utilized mixed research methods to conduct this study. The information was gathered via questionnaires and interviews. The experts have tested and validated these instruments. The data were then quantitatively and qualitatively analyzed. Quantitative data were analyzed with the aid of SPSS statistical calculations. In contrast, qualitative data were analyzed using multiple steps, including data reduction, data presentation, and conclusion. The results indicated that the majority of English teachers were prepared to implement online speaking instruction during a pandemic, despite the fact that some teachers were not quite prepared due to several obstacles. As for the challenges encountered by English teachers, there were online speaking assessments, poor connections, low interaction, and a lack of learning devices. Shortly, English teachers prepared to teach online speaking to students in order to improve the students' speaking ability, despite the emergence of certain obstacles.